DESAIN KARTU BERBASIS AUGMENTED REALITY (AR-CARD) SEBAGAI MEDIA PEMBELAJARAN BIOLOGI PADA MATERI BAKTERI - Winda Sari; Yustina Yustina; Zulfarina Zulfarina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The era of the industrial revolution 4.0 affected technology so thatdevelopment occurred very rapidly. This has an impact on all fields, including the worldof education. In the 2013 curriculum, teachers are required to integrate learning withadvances in technology, communication and information (ICT) to improve the quality ofeducation. But in reality, the learning process is still dominated by conventionallearning and the learning media used have not varied, and have not been integratedwith technology in accordance with the demands of the 2013 curriculum. Based on theexisting problems, this study aims to design Augmented Reality technology-basedlearning media integrated into the card. (AR-Card) on bacterial material. This researchis a descriptive study which consists of two stages, namely analysis and design. Theanalysis stage was carried out by observation using a questionnaire and the designstage was carried out by utilizing various computer software. The result of the researchis a card media design that is integrated with Augmented Reality, so that students cansee 3D AR biological abstract objects directly with this technology. These results areexpected to be developed and tested further.Key Words: Learning Media, Augmented Reality, AR-Card, Bacteria